From gene expression to causal associations: investigating the role of ferroptosis in cataract development - Chen Li; Xian-bing Yuan; Yi-cheng Lu; Zi-yue Song (BMC Medical Genomics)
Abstract Background Cataracts are one of the most prevalent blinding eye diseases globally, and ferroptosis may be involved in its pathogenesis; however, the precise mechanisms remain unclear. We therefore aimed to identify ferroptosis-related genes (FRGs) related to cataracts and assess their causal association. Methods We downloaded two gene expression profile datasets of patients with cataracts and gathered the FRGs from the MSigDB and GeneCards databases. This allowed us to find the ferroptosis-related differentially expressed genes (FRDEGs). The potential functions of these FRDEGs were explored using Kyoto Encyclopedia of Genes and Genomes (KEGG), gene ontology (GO), and gene set enrichment analysis (GSEA). A protein–protein interaction (PPI) network was established, and hub genes were screened. Additionally, potential diagnostic markers were identified by RT-PCR validation. Finally, a Mendelian randomization (MR) study was performed to ascertain the causal impact of FRDEGs on cataracts. Results Nineteen FRDEGs were identified by overlapping DEGs with FRGs. GO, KEGG and GSEA showed that the FRDEGs were associated with oxidative stress, IL17 signaling pathway, and glutathione metabolism. Nine hub genes were identified using the PPI network and five algorithms in Cytoscape. The RT-PCR results validated TIGAR, IL6, ATF3, and TNFAIP3 as potential biomarkers. Conclusion TIGAR and IL6 were identified to be causally associated with cataracts. Inverse variance weighting revealed that TIGAR decreased the risk of cataracts, whereas IL6 increased the risk of cataract. Our research identified ferroptosis-related hub genes in cataracts, providing valuable insights for pre-symptomatic diagnosis and contributing to our understanding of the molecular mechanisms of cataract risk genes.